Recruiting Intensity, Hires, and Vacancies: Evidence from Firm-Level Data - Eliza Forsythe; Russell Weinstein (Institute of Labor Economics (IZA), 2021)
We investigate employer recruiting behavior, using detailed firm-level data from a national survey of employers hiring recent college graduates. We show employers adjust recruiting effort, hiring standards, and compensation with the business cycle, beliefs about tightness, and their own hiring plans. We then show that firms expending greater recruiting effort hire more individuals per vacancy. The results suggest that when firms want to increase hires they adjust vacancies and recruiting intensity per vacancy, which may help explain the breakdown in the standard matching function during the Great Recession. Our measure of recruiting effort explains roughly 16% of the residual elasticity of the vacancy yield with respect to hires.
Keywords: J63; D20; E24; 330; recruiting intensity; vacancy yield; labor market search and matching; recent college graduates